Childhood cancer and emotional impacts on the family: A review of the literature (Research, Society and Development, 2021)
Childhood cancer, defined as cancer in children and adolescents aged 0-19 years, has profound impacts on everyone's lives, being a great inducer of negative feelings in children, adolescents and those close to them. So, the aim of the present review is to analyze the emotional impacts of childhood cancer on the family, discussing the different feelings aroused in the family nucleus by the treatment process and eventual cure of childhood cancer. This study is structured by an integrative literature review, based on the elaboration of the following guiding question: “What are the emotional impacts of childhood cancer on the family?”; the definition of databases such as PUBMED, SCIELO and VHL that served as a research instrument; based on the descriptors: Neoplasm, Child, Family, Emotions and the eligibility criteria for the review. Regarding the results, families reported numerous impacts on the Family such as psychological disorders, difficulties in relationships between parents and the change in family dynamics due to the treatment of children with pediatric cancer. Therefore, among the negative emotions, fear, irritability, anxiety, uncertainty and sadness stood out; as for the positive ones, resilience, social support, faith, hope, openness, love and positivity.  The diagnosis and subsequent treatment of childhood cancer is a very delicate moment for the whole family and psychological support for the child and the family is essential to minimize the harmful effects caused by bad feelings and expand the reach of good feelings.